A Preclinical study of role of Arishta Namak Dhoop in immunosupressed diseases - Mendhekar, Dr. Kiran; V. Kashikar sir, Dr. Shrikant (International Journal of Innovative Research in Medical Science, 2016)
Ayurveda is a science of life which not only cures the disease but also prevents many diseaseswith the help of different treatment modalities mentioned in dinacharya and rutucharya. Dhupana is one of the important karma for prevention of various diseases caused by microorganisms. In Kashyap Smahita, there is a detail study of dhupana karma under Dhup Kalpa Adhyay. Here an attempt to prove the role of Arishta Namak Dhoop in diseases which are caused by microorganisms in current lifestyle.